FORECASTING THE GOLD JEWELRY SALES USING SINGLE EXPONENTIAL SMOOTHING METHOD - Nur Ariza; Nuriadi Manurung; Masitah Handayani (Jurnal Teknik Informatika (Jutif), 2022)
Gold is a precious metal that plays an important role in people's daily lives. People use gold jewelry as a dowry so that gold is sought after, such as earrings, necklaces, pendants, bracelets, rings and others. However, buying and selling gold jewelry at a gold jewelry store has a different strategy. Gold sellers must carry out the gold jewelry production process to meet gold jewelry supplies and market demand. The results of the sale of gold jewelry sometimes increase and decrease every day which cannot be predicted every day, so this can affect the store to find out the profits and losses that will be obtained in the future. The purpose of this study was to determine the results of forecasting sales of gold jewelry at the Yoga Gold Shop using the single exponential smoothing method in the coming month. The results of this study resulted in March 2022 9 carat gold jewelry totaling 4191.16 grams with a 3.01% MAPE, 10 carat gold totaling 2095.53 grams with a 3.01% MAPE, Surabaya gold 1047.76 grams with a 3.03% MAPE and london gold jewelery 523.83 grams with a MAPE of 3.41%. So it can be concluded that applying the single exponential smoothing method can help in predicting the sales results of gold jewelry.